dari Toleransi ke Aksi: Peran Pelajar dalam Menghidupkan Kebhinekaan di Lingkungan SMK Negeri 1 Wonosegoro - Lany Kusumawati; Lathifah Sukma Sari; Laudya Saraswati; Pandu Veril Riyadi; Sri Budi Raharjo (Universitas Pahlawan Tuanku Tambusai, 2026)
Diversity is an important part of life, especially in vocational high schools. We must learn tolerance as a social skill that requires daily interaction with others at school. Today, tolerance and diversity are very important in education because they contribute to the development of a safe, peaceful, and harmonious life. The method used in this activity is to provide socialization to students. The implementation of activities to strengthen tolerance towards diversity values, which was carried out at SMK Negeri 1 Wonosegoro on Monday, November 24, 2025, by Boyolali University students who are taking the compulsory curriculum course (MKWK) went well and produced results in line with previous expectations, namely that the students of SMK Negeri 1 Wonosegoro were seen to appreciate differences and respect others in the school environment. This can be seen from the way they interact both inside and outside the classroom. Students are more open to the diversity of their peers' backgrounds.